A Decade of Research on Daptomycin - Taylor, Scott D. (Synlett, 2022)
Daptomycin is a calcium-dependent cyclic lipodepsipeptide antibiotic that is used in the clinic for treating serious infections caused by Gram-positive bacteria. In this account, I present a summary of the research that has been conducted in my group on daptomycin’s total chemical synthesis, its structure–activity relationships, and its mechanism of action, since we began our studies a decade ago.1 Introduction2 Solid-Phase Synthesis of Daptomycin by an On-Resin Cyclization3 α-Azido Acids and Alternative Routes to Daptomycin by On-Resin Cyclization4 Synthesis of Daptomycin by an Off-Resin Cyclization5 SAR Studies on Daptomycin6 Oligomerization of Daptomycin on Membranes7 The Chiral Target of Daptomycin8 SAR Studies on Phosphatidylglycerol9 Conclusions
Keywords: antibiotics; daptomycin; solid-phase synthesis; mechanism; structure–activity relationships